Development and characterization of 29 microsatellite markers for Ligumia nasuta (Bivalvia: Unionidae) using an Illumina sequencing approach. (June 2016) - Scott, Mariah W.; Hoffman, Jordan R.; Hewitt, Trevor L.; Beasley, Rochelle R.; Lance, Stacey L.; Jones, Kenneth L.; Morris, Todd J.; Zanatta, David T.
Abstract: Ligumia nasuta (Say, 1817; Eastern Pondmussel) is an imperiled freshwater mussel (Unionidae) in eastern North America. Population declines in the Laurentian Great Lakes resulting from the introduction of dreissenid mussels and habitat destruction in the 20th Century have greatly reduced and limited its distribution. To properly inform restoration and management efforts for L. nasuta, fine-scale genetic analyses must be performed on the remnant populations. This study used Illumina paired-end shotgun sequencing to identify potential microsatellite loci for L. nasuta, utilizing two samples to develop the Illumina paired-end shotgun library. Forty-eight primer pairs were tested on the remaining 24 samples. Twenty-nine of the 48 microsatellite primer sets screened were successfully amplified using 24 L. nasuta samples collected from the Great Lakes watershed. The estimated fragment size ranged from 167 to 445 base-pairs (bp) and the number of alleles per locus varied between 5 and 16 (mean = 9.7). Only five of the loci deviated significantly from Hardy–Weinberg expectations after Bonferroni corrections. The development of these new microsatellite loci will greatly facilitate future genetic studies on L. nasuta . Highlights: Microsatellite loci identified from two specimens using Illumina sequencing. 48 primer pairs tested for amplification success on 24 Ligumia nasuta specimens. 29 loci were successfully screened and characterized.